2018
DOI: 10.1016/j.socscimed.2018.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and the jilted generation: Using age-period-cohort analysis to assess differential trends in young people's mental health following the Great Recession and austerity in England

Abstract: Those born in the United Kingdom post-1979 have been described as a ‘jilted generation’, materially disadvantaged by economic and social policy; however, it is unclear whether this resulted in their experiencing poorer mental health than previous cohorts. Following the 2008 recession, UK austerity reforms associated with worsening mental health also disproportionately impacted those of younger working-age. This study aimed to identify any historic cohort changes in population mental health, and whether austeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…Even though the results presented in this systematic review showed no difference between income level of the countries and CMD, further studies with this focus are needed in order to deepen the knowledge about the subject. Longitudinal studies such as the British Household Panel Survey (BHPS) and Longitudinal Study of Young People in England (LYSPE) demonstrate the impact of economic recession and poverty in populations by strong associations between socioeconomic variables and health outcomes [76,[108][109][110][111].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the results presented in this systematic review showed no difference between income level of the countries and CMD, further studies with this focus are needed in order to deepen the knowledge about the subject. Longitudinal studies such as the British Household Panel Survey (BHPS) and Longitudinal Study of Young People in England (LYSPE) demonstrate the impact of economic recession and poverty in populations by strong associations between socioeconomic variables and health outcomes [76,[108][109][110][111].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 43 studies (200 980 participants; 19 countries) were included. The CMD prevalence studies were conducted in Asia [26,27,34,39,40,45,[48][49][50][52][53][54]57,70,89,90], America [38,41,44,84], Africa [22], Europe [24,28,32,[35][36][37]43,46,47,56,63,65,68,71,76,88,92] and Oceania [66,83]. The majority of studies (n = 33) had a cross-sectional design.…”
Section: Study Selectionmentioning
confidence: 99%
“…31 It is worth noting that this more recent decline in mental health among women occurs after a period of austerity, during which women's mental health had already been showing adverse trends. [32][33][34] The reduction in smoking, despite the adverse societal circumstances, may illustrate the importance of the availability of these products in influencing behaviour. There is an increasing evidence base which suggests that availability of unhealthy commodities drives consumption and contributes to health inequalities.…”
Section: Cigarette Smoking and E-cigarette Usementioning
confidence: 99%
“…These aforementioned challenges have contributed to the emergence of a "crisis" in children's mental health and emotional wellbeing (Thomson & Katikireddi, 2018). Indeed, self-reporting suggests that as few as 30% of young people feel they have "good" overall wellbeing (Prince's Trust, op cit); and a quarter of 14 year old girls report experiencing high levels of depressive symptoms (Patalay & Fitzsimons, 2018).…”
Section: Diagnosing Colicmentioning
confidence: 99%